Pemanasan dan Konsentrasi Tepung Maizena dalam Pembuatan Saus Tomat - Nur Rahmah; Annisa Aulia Ramadhani Hidayat (Seminar Nasional LP2M UNM, 2022)
Abstrak. Tomato is a horticultural commodity of the fruit vegetable group that is widely consumed by the community with data on tomato production in Indonesia reaching 1,508,404 tons. In general, people understand that tomatoes are a high enough source of vitamin C so that tomatoes are widely used, not only processed as vegetables but also processed as a variety of food sources, one of which is processed into sauce products. The purpose of this study was to determine the process of making tomato sauce and chili sauce and to determine the effect of using additional ingredients and processing the resulting tomato sauce and chili sauce. The research method was designed with a combination of heating time and cornstarch concentration, including: 111) 5 minutes, 20 grams; 112) 10 minutes, 25 grams; 113) 15 minutes, 30 grams; 114) 20 minutes, 35 grams; and 115) 25 minutes, 40 grams. The best treatment averages for all test parameters were obtained from 112 and 113. The results showed that the tomato sauce manufacturing process consisted of sorting, blanching at a temperature of 80-90℃, heating tomatoes, adding seasonings and food additives, and adding cornstarch at 60℃. The pH of tomato sauce decreases with the length of the heating process.